Dynamic Impacts of Energy Consumption on Agricultural Growth in Iran and Selected Developing Countries - Papi, Amin; Moghaddasi, Reza; Mousavi, Nematollah; Zeraatkish, Yaaghoob (International Journal of Energy Economics and Policy, 2025)
Many countries across the globe are facing difficulties in meeting energy demand in their production sectors. Non-renewable feature of fossil fuels necessitates enhancing their efficiency in all economic sectors including agriculture. Touching this goal, requires reliable evidence on the impact of energy on sectoral economic growth. This study aims at estimation of the effect of energy use on agricultural growth in selected developing and developed nations. We applied country panel data, conventional parametric and non-parametric approaches as our materials and methods. Our findings show that the impact of energy use on agricultural growth varies over time in both groups of countries indicating its dynamic influence. In addition, the non-parametric approach captures such an impact in a better manner. Keeping sustainable growth and environmental concerns in mind, agricultural energy efficiency promotion in high carbon dependent countries through technology investment is recommended.